Peran Job Satisfaction Dalam Memediasi Delay Of Gratification Terhadap Work Engagement Pegawai (Studi pada Dinas Koperasi UMKM Kota Denpasar) - Jagatdita, Cahaya; Surya Putra, Made (Innovative: Journal Of Social Science Research, 2024)
Work engagement is one of the crucial factors in assessing employee well-being, productivity, and performance, encompassing their involvement and enthusiasm in carrying out their tasks. Work engagement reflects the extent to which employees feel motivated, committed, and involved in their work, which ultimately can influence both individual and organizational performance. This research aims to examine and explain the role of job satisfaction in mediating delay of gratification on employee work engagement. The study was conducted among employees of the Dinas Koperasi UMKM Kota Denpasar, with a sample size of 58 employees obtained using a saturation sampling method. Data collection was carried out through interviews and questionnaires. The data analysis techniques used in this research is Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) approach. The results of the analysis shows that: 1) delay of gratification has a positive and significant effect on employee work engagement, 2) delay of gratification has a positive and significant effect on employee job satisfaction, 3) job satisfaction has a positive and significant effect on employee work engagement, 4) job satisfaction mediates the relationship between delay of gratification and employee work engagement. The theoretical implication of this research supports the findings of previous studies through the perspective of Expectancy Theory. The practical implication of this research provides policy guidelines for agency leaders and employees to improve employee work engagement through delay of gratification and job satisfaction.